Penguatan Strategi Pemasaran UMKM Gethuk Magic Ditengah Keterbatasan SDM dan Laporan Keuangan di Era Digital - Pranata, Mohammad Firlie; Fakhri, Ahmad Alauddin; Fakhri, Defyandi; Afiyah, Wardaniatul; Azzahrah, Fatimah; Islami, Siti Nur Azizah Nikmah; Pranata, Rendi; Sya’ban, Purnama (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The Gethuk Magic MSME in Babbalan Village, Sumenep, faces significant challenges in human resource (HR) management and financial reporting, particularly in the digital era that demands rapid adaptation to technology. This study aims to strengthen the digital marketing strategy of the MSME to enhance its competitiveness and expand market reach. A qualitative descriptive approach was used, employing Participatory Action Research (PAR) and case study methods, including interviews, observations, and direct field documentation. The research findings indicate that interventions through training in digital media usage and financial recording applications have improved operational efficiency and product visibility. Offline marketing activities integrated with digital promotion have proven effective in increasing consumer interaction and sales turnover. These findings affirm that technology-based marketing strategies, along with improved HR capacity and digitalized financial reporting, are strategic solutions for addressing the limitations faced by MSMEs in an increasingly competitive digital economy.